Assessment of an educational intervention based on constructivism in nursing students from a Mexican public university - Jiménez Trujano, Laura; Morán Peña, Laura (Investigación y Educación en Enfermería, 2015)
Objective. This work sought to evaluate the effect of an educational intervention centered on the analysis of clinical cases to inquire on conceptual learning in students on the theme of nursing care of women with complicated puerperium. Methodology. This was a quasi-experimental study with before and after evaluation. Two groups of students participated from the eighth semester of the nursing program, which professionalized individuals who were already nursing technicians: the study group (n = 33) was taught the theme of nursing care to women with complicated puerperium with the case analysis technique and the control group (n = 27) received traditional teaching. A self-applied question here was used related to the thematic unit, which included three clinical cases and the resolution of a total of 37 questions related to set cases. This questionnaire was the same applied before and after the intervention. Results. The pre-intervention mean score was similar in both groups (26 during the study and 27 during the intervention). Upon completing the educational intervention, the post-intervention scores were equal in both groups (27 points). The intra-group analysis showed that in the study group the intervention produced a slight change in conceptual learning, which was statistically significant. During the post-hoc analysis differences in scores were found in students who worked in hospitals with tier three level of care. Conclusion. Educational intervention favored conceptual learning slightly in the study group. It is necessary to explore other intervening variables that propitiate this learning in the program. How to cite this article: Jiménez TL, Morán PL. Assessment of an educational intervention based on constructivism in nursing students from a Mexican public university. Invest Educ Enferm. 2015; 33(3):